Legal translation and “traditional” comparative law – Similarities and differences - Simonnæs, Ingrid (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
The aim of this paper is to describe some similarities and differences encountered when comparing legal translation and comparative law as separate yet interrelated disciplines. To this end, their respective objectives and methods are broadly outlined. This is followed by a case study on translations of a specific legal text into English and German which have been produced by candidates sitting the Norwegian National Translator Accreditation Exam. In this paper, I intend to show that comparative law “in the traditional sense” (Friedman, 1990, p. 49) is much concerned with issues of translation and show that there are not only similarities but also differences.